Estimasi Sumberdaya Batubara Dengan Menggunakan Metode Ordinary Kriging di CV. NISKA Dusun Senamat, Kecamatan Pelepat, Kabupaten Bungo, Provinsi Jambi - iskandar iskandar; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2023)
Abstract.  CV. NISKA is a company engaged in mining, especially coal, which has a mining business permit area of around 199 hectares. This company is located in Senamat Hamlet, Pelepat District, Bungo Regency, Jambi Province. CV. NISKA open pit mining system with the Open Pit method, which is a mining method that digs up mineral deposits that exist in a rock that is located at or close to the surface. Therefore it is necessary to estimate the resources in the area. Resource estimation is an estimate or estimation of the amount of resources in a place. Estimation of coal resources is a basic thing that must be done in coal mining activities. One method that can be used in estimating coal resources is the geostatistical method. The geostatistical method is the application of statistical sciences to explain earth science phenomena, especially in the fields of mining and geology. Some of the analyzes performed in estimating coal resources using the ordinary kriging method include univariate statistical analysis, spatial statistical analysis, ordinary kriging block estimation, geological modeling of coal deposits and calculation of coal tonnage. Based on the type of data to be obtained, technical data analysis uses quantitative data, namely by processing data using mining software. Then displays the design form in three dimensions. Based on the analysis and discussion that has been carried out, the research results can be taken, namely the correlation of the original thickness with ordinary kriging has a correlation value of 0.9106, which means that the two variables have a strong relationship. Total tonnage of coal resources in the PT. NISKA is a number of 2,349,750 ton.Keywords: CV.NISKA, Estimation, Kriging .